Candi, Space and Landscape : a Study on the Distribution, Orientation and Spatial Organization of Central Javanese Temple Remains. - Degroot, V. M. Y. (Mededelingen Van Het Rijksmuseum Voor Volkenkunde., 2010)
Central Javanese temples were not built anywhere and anyhow. On the contrary: their positions within the landscape and their architectural designs were determined by socio-cultural, religious and economic factors. This book explores the correlations between temple distribution, natural surroundings and architectural design to understand how Central Javanese people structured the space around them, and how the religious landscape thus created, developed. Besides questions related to territory and landscape, Degroot's book analyzes the structure of the built space and its possible relations with.